The migratory locust (Locusta migratoria) as a potential source of protein and biopolymer compounds in the future - YASINTA LETEK KLEDEN; LINCE MUKKUN; MELYCORIANDA HUBI NDAPAMURI; FADLAN PRAMATANA (Society for Indonesian Biodiversity, 2023)
Abstract. Kleden YL, Mukkun L, Ndapamuri MH, Pamatana F. 2023. The migratory locust (Locusta migratoria Meyen) as a potential source of protein and biopolymer compounds in the future. Biodiversitas 24: 5979-5987. The migratory locust Locusta migratoria Linnaeus 1758, is an edible insect posing significant challenges to the agricultural industry in Indonesia, particularly in East Nusa Tenggara (ENT) Province. However, apart from the status of the migratory locust as a highly destructive insect pest, it has great potential as a source of protein, amino acids, and other bioactive compounds. This study aimed to determine the nutritional and other bioactive characteristics of locusts. Proximate analysis was performed using SNI 01-2891-1992 to identify protein, fat, ash, carbohydrates, and energy. The amino acid analysis was conducted using Ultra Performance Liquid Chromatography (UPLC). The chitin from the nymph and imago stages of the locust was obtained through a process including demineralization and deproteinization. Subsequently, the chitin was subjected to deacetylation in order to obtain chitosan. Proximate content analysis shows that locust has promising potential as a source of nutrients in order to address the nutritional problems of the population that are still a problem in Indonesia including in ENT Province. The protein content of locust ranged from 63.72 to 75.26% dry weight. These contents are close to those of egg protein (83%), beef protein (85%), and even most plant proteins, like soybean (81%). The imago stage exhibited the highest total amino acid content, measuring 411.41 mg/100 g, with essential amino acids such as lysine, isoleucine, leucine, valine, phenylalanine, threonine, histidine, and tryptophae. Imago contains chitin from 8.79 to 12.05% dry weight and chitosan from 59.3% to 71.26% by weight of chitin. The study suggests that locusts can be an alternative source of nutrition to dial with stunting in term of their availability of protein and amino acid. Additionally, chitin and chitosan in migratory locusts are promising nutrient sources for agriculture and health applications.